Exploring the factors of e-commerce adoption Covid-19 pandemic among small business - Kuguna Sundari Partiban; Mohd Jazali Farhan Mohd Rizal; Nur Aishah Nabilah Mohd Shamsudin; Siti Maimunah Mokhtar (2023)
The Coronavirus impact many factors including e-commerce, technology, business travel, and the economy. Thus, this study aims to explore the factors of E-commerce in the Covid-19 pandemic among small business. The research employed qualitative method through in-depth interviews. It used a thematic analysis and five small business entrepreneurs in Kelantan as its participants. The researcher employed non-probability sampling. Judgmental or purposive sampling was utilized based on the researcher's views of who will provide the greatest information to fulfil the researcher's aims. Finding of the study showed that government support, social media influence and logistic and technology have an impact among small business e-commerce adoption during and after Covid-19. This study has significant policy implications for governments and decision-makers, who should create plans to offer more small business financial assistance, advice, and training to improve the e-commerce adoption.